The constituents of Castilleja rhexifolia, Mahonia repens and Oncidium cebolleta - Suess, Terry R., author; Stermitz, Frank R., advisor (Colorado State University. Libraries, 1981)
A total of 54 species of plants from 21 different plant families were collected throughout the subalpine region of the Colorado Rocky Mountains. These plants were tested for antitumor activity, alkaloid content and grasshopper antifeedant activity. Although none of the plants showed significant antitumor activity, 13 showed the presence of alkaloids and eight showed activity in the grasshopper antifeedant screen. One of the plants that showed the presence of alkaloids was Castilleja rhexifolia Rydb. Investigation of C. rhexifolia extracts led to the isolation of senecionine, a previously reported hepatoxic, pyrrolizidine alkaloid. This is the first report of a pyrrolizidine alkaloid in the Scrophulariaceae, and the first alkaloid isolated from Castilleja. The constituents of Mahonia repens (Lindl.) G. Don, a plant used by the Ramah Navajo of the Southwest in folk medicine, were also investigated. The leaves of M. repens contained four known aporphine alkaloids: isocorydine, corydine, thaliporphine and glaucine. The stems and roots of M. repens contained one known aporphine alkaloid (magnoflorine), four known bisbenzylisoquinoline alkaloids (obaberine, thalrugosine, oxyacanthine and obamegine), four known protoberberine alkaloids (palmatine, berberine, jatrorrhizine and columbamine), the known lignan, syringaresinol, and the sugar, sucrose. The isolation of these secondary metabolites allows a chemotaxonomic comparison of M. repens to the other Mahonia sp. studied, and also to the closely related genus, Berberis. As part of a continuing study to clarify the spectral data of 1,2,10,11-dihydroxydimethoxyaporphines, N-methylisocorytuberine was synthesized by the Pomeranz-Fritsch reaction and Pschorr cyclization. Spectral and thin layer chromatography data for N-methylisocorytuberine were then compared to two other reported isomers, magnoflorine and N,N-dimethyllindcarpine. The orchid, Oncidium cebolleta (Jacq.) Sw., is used by the Tarahumara Indians of Mexico as an important substitute for peyote. The chloroform extract of O. cebolleta was found to contain five previously unreported phenanthrenes and 9,10-dihydrophenanthrenes. Four of these compounds were identified as 2,3-dihydroxy-4,6,7 -trimethoxyphenanthrene, 2,3-dihydroxy-4,6,7-trimethoxy-9,10-dihydrophenanthrene, 2,7-dihydroxy-3,4-dimethoxyphenanthrene and 2,8- dihydroxy-4,7-dimethoxyphenanthrene. Although it is not known if these compounds are responsible for the hallucinogenic activity of O. cebolleta, their structural similarity to tetrahydrocannabinol makes this conceivable.
Covers not scanned.
Keywords: Plants -- Analysis; Cancer -- Research; Botany -- Colorado